Józef Mehoffer’s competition design for the polychrome decoration of the Franciscan Church in Kraków, 1894. An attempt to reconstruct the artist’s decorative concept - Beata Studziżba-Kubalska (Sacrum et Decorum, 2023)
Józef Mehoffer’s competition design for the painting decoration of the Franciscan Church in Kraków in 1894 has not yet been found. This article is an attempt to reconstruct the artist’s decorative concept on the basis of the surviving sketches for the project, as well as notes drawn and written in a sketchbook from 1893–1894. The artist, who was in Paris in February 1894, heard about the competition from Tadeusz Stryjeński. The project he sent to the jury in May 1894 did not meet the formal requirements; it was too sketch-like and unpolished and was not accepted. Mehoffer began work on it with detailed studies of sources and iconography, documented by his drawings and notes in his sketchbook. These bear witness to his technical dependence on Jan Matejko and the painters of the historicist school. The artist’s meticulous approach in this respect was perhaps one of the reasons why the project was not completed within the three-month deadline set by the jury. A stylistic analysis of Mehoffer’s sketches for the decoration of the Franciscan Church leads to the conclusion that they were created under the influence of Matejko’s polychrome decoration of the presbytery of St Mary’s Church in Kraków, as well as other sacral decoration of the second half of the 19th century, associated with the current of academic historicism – an important model for the Polish artist was undoubtedly the polychrome decoration of the chapels of Notre Dame Cathedral in Paris – by Eugène Viollet-le-Duc and Maurice Ouradou. Mehoffer owed much of his inspiration for the iconography of his design, in which the dominant motifs were depictions of 13th-century Polish saints, nuns, female rulers and Piast princes, to Matejko’s work, The Defeat of Legnica – The Rebirth of Poland. 1241, 1888. The overall vision for the decoration of the Franciscan Church, which he did not include in the competition design but described in his notes, went beyond historicism. It demonstrates the artist’s sensitivity to the new trends in art at the turn of the 20th century, and the fact that he was already aware of the profound changes taking place in the style of monumental painting and in the perception of its function.